Structure–activity relationship studies on 2, 5, 6-trisubstituted benzimidazoles targeting Mtb-FtsZ as antitubercular agents. Issue 1 (16th October 2020) - Haranahalli, Krupanandan; Tong, Simon; Kim, Saerom; Awwa, Monaf; Chen, Lei; Knudson, Susan E.; Slayden, Richard A.; Singleton, Eric; Russo, Riccardo; Connell, Nancy; Ojima, Iwao
Abstract : Filamenting temperature sensitive protein Z (FtsZ) is an essential bacterial cell division protein and a promising target for the development of new antibacterial therapeutics. Abstract : Filamenting temperature sensitive protein Z (FtsZ) is an essential bacterial cell division protein and a promising target for the development of new antibacterial therapeutics. As a part of our ongoing SAR studies on 2, 5, 6-trisubstituted benzimidazoles as antitubercular agents targeting Mtb -FtsZ, a new library of compounds with modifications at the 2 position was designed, synthesized and evaluated for their activity against Mtb -H37Rv. This new library of trisubstituted benzimidazoles exhibited MIC values in the range of 0.004–50 μg mL −1 . Compounds 6b, 6c, 20f and 20g showed excellent growth inhibitory activities ranging from 0.004–0.08 μg mL −1 . This SAR study has led to the discovery of a remarkably potent compound 20g (MIC 0.0039 μg mL −1 ; normalized MIC 0.015 μg mL −1 ). Our 3DQSAR model predicted 20g as the most potent compound in the library.